Water Quality Assessment Based on HFB I& BMWP Index In Karoon River ,Khouzestan Provience, (Northwest of Persian Gulf) - Sahar Jalili (Anthropogenic Pollution)
Score-based biotic indices are widely used to evaluate the water quality of streams and rivers. The main objective of this study was the assessmentof the water quality of Karoon River throught biotic indices based on the Family Biotic Index (HFBI), and the Biological Monitoring Working Party Score System (BMWP). Macroinveratabrate communities are one of the most used groups in assessment of water quality, since they respond directively to the level of contamination of aquatic ecosystems. Sampling were performed in 4 stations (Menikh, Zhian Canal, Bahrakani and Dahaneh). Sampling was carried in each station over one year ( winter, spring, summer and autumn). Macroinvertebrates were collected by the grab quantitative sampller. Four phylaum (Nematoda, Annelidae, Mollusca and Arthropoda) distributed amoung 11 families were sampled. Station1 (Menikh) had the highest Macroinveratabrate diversity and richness. The highest density of aquatic invertabrates were recorded in winter (Annelidae 46%, Crustacea 28% ,Mullusca 21% and Diptera 5% ) and spring ( Mullusca 58%, Crustacea 27%,Nematoda 10% and Anellidae 5%) respectively. The BMWP index showed that the water quality was in the reguallar category (for Menikh, Zhian Canal and Bahrakani) and in the poor category (for Dahaneh). HFBI index pointed out the water quality was in the reguallar catagorry (for Menikh, Zhian Canal and Bahrakani) and poor category (for Dahaneh) . Biotic indices used reflected the changes to the water quality.